Incidence of severe rise in intraocular pressure after intravitreous injection of aflibercept with prefilled syringes - Dingerkus, Vita; Somfai, Gabor Mark; Kinzl, Stephan; Orgül, Selim Ismet; Becker, Matthias D.; Heussen, Florian Moritz (Scientific reports, 2022)
Our aim was to analyze the intraocular pressure (IOP) changes following different intravitreous injection (IVI) procedures with or without prefilled syringes (PFS) and to elaborate their possible causes. Clinical study and laboratory assessment. 173 eyes of 141 patients. The IOP was prospectively measured pre- and postoperatively in three groups of patients receiving IVI either with ranibizumab (RP), aflibercept PFS (AP) or aflibercept vials (AV). The AP emptying volume (EV) was assessed using 40 aflibercept PFS vials: the plunger was aligned precisely (normal volume, NV) or right below the indication line (high volume, HV) and the drug was ejected with (wP) or without forced pressure (nP). Primary outcome was post-treatment IOP with type of IVI and pre-treatment IOP as fixed factors. Secondary outcome was identification of possibly confounding factors (age, sex, pathology, presence of pseudophakia, spherical error, and number of injections) and IOP > 30 mmHg post-treatment. An IOP rise above 30 mmHg was observed in 8/38 (22%), 16/51 (31%) and 35/86 (41%) cases in the RP, AV and AP groups, respectively (p = 0.129). Pre-treatment IOP was the only predictive variable for IOP rise (p < 0.001). The EV values in the NVnP, NVwP, HVnP and HVwP groups were 56.06 ± 10.32, 70.69 ± 4.56, 74.22 ± 7.41 and 81.63 ± 3.67 µl, respectively (p < 0.001). We observed a marked, although not significantly higher incidence of IOP elevations with the aflibercept PFS. One possible reason may be the error-proneness of administering the correct volume with the AP. Caution should be taken when using the aflibercept PFS in order to prevent potential optic nerve damage in cases with marked elevation in IOP.